2020
DOI: 10.1186/s12882-020-02025-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq identifies condition-specific biological signatures of ischemia-reperfusion injury in the human kidney

Abstract: Background Acute kidney injury (AKI) is defined as a sudden event of kidney failure or kidney damage within a short period. Ischemia-reperfusion injury (IRI) is a critical factor associated with severe AKI and end-stage kidney disease (ESKD). However, the biological mechanisms underlying ischemia and reperfusion are incompletely understood, owing to the complexity of these pathophysiological processes. We aimed to investigate the key biological pathways individually affected by ischemia and reperfusion at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…Semaphorin-plexin signalling has already been shown to be dysregulated in IR in mice, impairing the integrity of the slit diaphragm [74,77]. Additionally, an RNA-Seq study demonstrated the downregulation of KRAS and another isoform of plexin (PlxnB1) in the human kidney after IR injury [78]. Despite the upregulated miRNAs in our study, PlxnA2 was not suppressed 10 days after IR, but it was upregulated.…”
Section: Discussioncontrasting
confidence: 62%
“…Semaphorin-plexin signalling has already been shown to be dysregulated in IR in mice, impairing the integrity of the slit diaphragm [74,77]. Additionally, an RNA-Seq study demonstrated the downregulation of KRAS and another isoform of plexin (PlxnB1) in the human kidney after IR injury [78]. Despite the upregulated miRNAs in our study, PlxnA2 was not suppressed 10 days after IR, but it was upregulated.…”
Section: Discussioncontrasting
confidence: 62%
“…Next-generation sequencing (NGS) has been widely used to reveal the potential biomarkers and molecular mechanisms of AKI. In ischemia–reperfusion (I/R) kidney injury, RNA-seq from five pairs of human normal and I/R kidney tissues revealed that apoptosis-, metabolism-, and fibrosis-related pathways were dysregulated in I/R tissues ( Park et al, 2020 ). Another cohort of RNA sequencing data found that apoptosis, migration, oxidation–reduction, and proliferation of macrophages were involved in I/R injury.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of RNA-sequencing (RNAseq) has allowed for transcriptome-wide analyses that identify the biological pathways that are implicated in the pathophysiology of various diseases. Multiple studies have utilized RNAseq to identify novel mechanisms of AKI, including the critical genes involved in kidney disease progression and recovery in the last few years [72][73][74][75][76]. Park et al used RNAseq to identify the gene expression changes that occur in multiple phases of in human AKI, including pre-ischemia, during ischemia, and during reperfusion [74].…”
Section: Metabolic Derangementsmentioning
confidence: 99%
“…Multiple studies have utilized RNAseq to identify novel mechanisms of AKI, including the critical genes involved in kidney disease progression and recovery in the last few years [72][73][74][75][76]. Park et al used RNAseq to identify the gene expression changes that occur in multiple phases of in human AKI, including pre-ischemia, during ischemia, and during reperfusion [74]. Interestingly, dysregulated metabolism and apoptotic pathways were found in the ischemic phase of injury, while cell growth and innate immune pathways were involved in the reperfusion phase.…”
Section: Metabolic Derangementsmentioning
confidence: 99%